If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17(t + -4) + 4t = 7(3t + 3) + -10 Reorder the terms: 17(-4 + t) + 4t = 7(3t + 3) + -10 (-4 * 17 + t * 17) + 4t = 7(3t + 3) + -10 (-68 + 17t) + 4t = 7(3t + 3) + -10 Combine like terms: 17t + 4t = 21t -68 + 21t = 7(3t + 3) + -10 Reorder the terms: -68 + 21t = 7(3 + 3t) + -10 -68 + 21t = (3 * 7 + 3t * 7) + -10 -68 + 21t = (21 + 21t) + -10 Reorder the terms: -68 + 21t = 21 + -10 + 21t Combine like terms: 21 + -10 = 11 -68 + 21t = 11 + 21t Add '-21t' to each side of the equation. -68 + 21t + -21t = 11 + 21t + -21t Combine like terms: 21t + -21t = 0 -68 + 0 = 11 + 21t + -21t -68 = 11 + 21t + -21t Combine like terms: 21t + -21t = 0 -68 = 11 + 0 -68 = 11 Solving -68 = 11 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 5(x-2)-8xd=-34 | | 89-6=56-3 | | -1450-8x=-12 | | -3(2s-6)-18=-2(7s+7)-2 | | f(4)=-3x-1 | | Fx=-3x-1 | | 7i+(-2-i)= | | -3(x-1)+10=2x-20 | | 64-.05x=0 | | X+8X=130 | | 7-a=6-a | | -2(2s-6)-12=-2(9s+0)-3 | | 3(x-2)+2(x+1)-(1)=0 | | 5x+2+6x+8=10+5 | | -1/6(x-12)+1/3(x+3)=x-7 | | 7+x=3x-13 | | x-5=-3x-5 | | 64-.05x=20 | | 4(5-a)-3(a+4)=10 | | H/4+5=-1 | | 3(x+7)/2=19 | | 5(x+5)=4(x-5)+x | | 25+j/2=15 | | 2(1-1)=3(a+1) | | -3h-11=-5 | | 7x^2-3=60 | | 2z+10=-5 | | 6t+u=63 | | -6x+25y+9=0 | | 4=-2(-3+f) | | k/6-5=-2 | | 6a-4a+6=8-2a |